Book review: Against therapy: Emotional tyranny and the myth of psychological healing (1988): by Jeffrey Masson - Cloete, Nico (PINS-Psychology in Society, 2025)
An archive of the misdemeanours of psychotherapy The following two passages come from the conclusion of Jeffrey Masson’s latest book entitled Against therapy: Emotional tyranny and the myth of psychological healing: "Every therapy I have examined in this book (with the exception of radical and feminist therapies, which are beset with other problems) displays a lack of interest in social injustice. Each shows a lack of interest in physical and sexual abuse. Each shows an implicit acceptance of the political status quo. In brief, almost every therapy shows a certain lack of interest in the world" (p240); "Psychotherapy cannot be reformed in its parts, because the activity, by its nature is harmful. Recognizing the lies, the flaws, the harm, the potential for harm, the imbalance in power, the arrogance, the condescension, the pretensions may be the first step in the eventual abolition of psychotherapy that I believe is, one day in the future, inevitable and desirable" (p254). From the above quotes it is clear that the controversial author of The assault on truth: Freud’s suppression of the seduction theory (1984) (for which he was fired as archivist of the Freud library) and A dark science: Women, sexuality and psychiatry in the nineteenth century (1986) should be prepared for another salvo from the multi-billion dollar profession that "profits from other people’s misery" (p239). The argument against therapy consists mainly of identifying a fundamental theoretical flaw that underlies all therapy, of illustrations of the abuse of clients and the reactionary politics of certain prominent therapists.